The End of This World: Climate Justice in So-Called Canada - Gabrielle McLaren (Engaged Scholar Journal)
Book review: Angele Alook, Emily Eaton, David Gray-Donald, Joël Laforest, Crystal Lameman and Bronwen Tucker. The End of This World: Climate Justice in So-Called Canada. 2023. Toronto. Between the Lines. 219 pages. $29.95 (paperback), ISBN 9781771136129.